Impact of Control and Trust on Megaproject Success: The Mediating Role of Social Exchange Norms. (23rd January 2019) - Wang, Dedong; Fang, Shaoze; Fu, Hongwei
Abstract : Trust and control are the two main governance mechanisms in megaprojects. However, the role of social exchange norms in trust and control governance remains unclear. Based on social exchange theory, we explored the impact of control and trust on megaproject success by considering the mediating effect of social exchange norms, which include reciprocity, negotiation, and information sharing. Partial least squares structural equation modeling was used to test the hypotheses based on data collected from 155 respondents. Results show that control and trust have positive effects on megaproject success. Trust can promote social exchange norms. That is, the higher the level of trust is, the greater the likelihood that reciprocity, negotiation, and information sharing will increase. Control does not have a significant impact on social exchange norms. Social exchange norms have a mediating effect on the relationship between trust and megaproject success but not on the link between control and megaproject success. Our findings fill in the gaps in the literature on megaproject governance and contribute to the development of megaproject management theory, which can help project managers understand the motivation orientations of all parties to make decisions wisely and rationally under complex environments.